Improved Performance of Water Supply System Sawah Liek and Tungku Sadah PDAM Kota Padang Panjang - Ridwan Ridwan (Fakultas Teknik, 2021)
Sawah Liek and Tungku Sadah have increased turbidity during the rainy season, 629 NTU. Sawah Liek and Tungku Sadah are 845 m and 888 m above sea level and flow by gravity at Sungai Andok Reservoir, 802 m. Sawah Liek has a production of 5 l/s for 428 customers and Tungku Sadah 10 l/s for 2,806 customers. One of the causes of turbidity fluctuation during rain is planting activities which degrade the area of land cover, increase runoff and minimize infiltration into the area that the flow from the source decreases every year. Water consumption for customers of Sawah Liek is 202 l/person/day and Tungku Sadah 62 l/person/day is smaller than the category of small towns of 130 l/person/day. The installed slow sand filter is unable to handle the turbidity during the rain in exceeds of 50 NTU. The maximum produced by the installed slow sand filter is 2.67 l/s. Changes in the function of the filter installed at a high-speed sand filter can increase production to 26.7 l/s and overcome turbidity fluctuations can be accomplished by improving the system with a complete treatment facility or an incomplete processing facility consisting of a screen, a large chamber, coagulation, and flocculation, filtration and disinfection.